British Obesity Metabolic Surgery Society endorsed guidelines for psychological support pre‐ and post‐bariatric surgery. Issue 6 (11th September 2019) - Ogden, Jane; Ratcliffe, Denise; Snowdon‐Carr, Vanessa
Summary: Research teams have argued that some bariatric patients require psychological input pre‐ and post‐surgery and that weight loss surgery should only be undertaken by a multidisciplinary team (MDT) that can provide psychological support. To date, no guidelines exist for the provision of psychological support pre‐ and post‐bariatric surgery. The authors were approached by British Obesity Metabolic Surgery Society (BOMSS) in September 2017 to produce guidelines for the provision of psychological support for patients pre‐ and post‐bariatric surgery. These guidelines were developed using seven stages: (a) review of evidence base; (b) expert input; (c) feedback from BOMSS delegates; (d) feedback from the special interest group; (e) service user feedback; (f) presentation to BOMSS council; and (g) presentation to the Association for the Study of Obesity. The guidelines describe two stepped care service models for the delivery of psychological support pre‐surgery and 6 to 9 months post‐surgery involving online resources, group workshops and one‐to‐one with a clinical psychologist. They are founded upon the following principles: (a) a living document to be modified over time; (b) flexible and pragmatic; (c) advisory not prescriptive; (d) broad based content; (e) skills based delivery. These guidelines are feasible for use across all services and should minimize patient risk and maximize patient health outcomes.